The Hedonic Approach to Vineyard Site Selection: Adaptation to Climate Change and Grape Growing in Emerging Markets - Orley Ashenfelter (Institute of Labor Economics (IZA), 2017)
This paper shows how the hedonic approach to vineyard site selection can be used in the adaptation of vineyard land to climate change, natural disasters or other exogenous events. The basic idea is that, if the relation between weather and grape quality is known for each grape type in existing growing areas, then it is possible to predict the quality of grapes that would be produced in other locations, or in the same location with a changed climate. This permits the optimization of grape type selection for a location and also provides an indication of the value that a particular planting should produce. The relation of grape quality to the weather is provided for several well-known viticultural areas, including Burgundy, Bordeaux, Rioja, and the Piedmont. An application of the method to a new vineyard area in the Czech Republic following the demise of Communism is used to demonstrate the method.
Keywords: O21; Q16; Q18; 330; vineyard site; hedonic method; grape growing; climate change